2018
DOI: 10.3390/nano8030148
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Materials Based on Self-Assembling Peptides on Ti25Nb10Zr Alloy: Molecular Structure and Organization Investigated by Synchrotron Radiation Induced Techniques

Abstract: In this work, we applied advanced Synchrotron Radiation (SR) induced techniques to the study of the chemisorption of the Self Assembling Peptide EAbuK16, i.e., H-Abu-Glu-Abu-Glu-Abu-Lys-Abu-Lys-Abu-Glu-Abu-Glu-Abu-Lys-Abu-Lys-NH2 that is able to spontaneously aggregate in anti-parallel β-sheet conformation, onto annealed Ti25Nb10Zr alloy surfaces. This synthetic amphiphilic oligopeptide is a good candidate to mimic extracellular matrix for bone prosthesis, since its β-sheets stack onto each other in a multilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Depending on the type of bone, the modulus of elasticity varies between 4 to 30 GPa . Titanium and titanium alloys are recognized as good materials for orthopedic implants due to their osseocompatibility and bone‐bonding capacity . Currently used commercial titanium implants satisfy the required mechanical properties with a Young's modulus within the range of 100–120 GPa .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of bone, the modulus of elasticity varies between 4 to 30 GPa . Titanium and titanium alloys are recognized as good materials for orthopedic implants due to their osseocompatibility and bone‐bonding capacity . Currently used commercial titanium implants satisfy the required mechanical properties with a Young's modulus within the range of 100–120 GPa .…”
Section: Introductionmentioning
confidence: 99%
“…Nature always uses the simplest material blocks, which has rather meager properties, to design multi-scale materials with outstanding bio-functional properties, providing scientists with infinite inspiration to fabricate bio-inspired hierarchical structural materials using the simplest possible material blocks to achieve the highest performance. Molecular movement in some molecular devices can be effectively controlled by chemical methods like molecular rotary motors [ 11 ], synchrotron radiation-induced techniques [ 12 ], and molecular motors [ 13 ]. A mechanical technique using the simplest possible laminar flow has never been used before.…”
Section: Introductionmentioning
confidence: 99%
“…HAP samples were incubated in SAP solutions with pH values of 4 and 10 pH, as described in the experimental section. Previous investigations on SAP adsorption on the TiO 2 surface showed that the thickness of the peptide overlayer decreases with increasing pH of the mother solution [23,37]; however, in the 4-10 pH range, the thickness of the peptide overlayer remains approximately constant, and only at pH = 12 a significant decrease of the overlayer thickness can be observed [23]. On the other hand, the solubility of hydroxyapatite is expected to increase as the solution's pH decreases.…”
Section: Ftir and Xps Resultsmentioning
confidence: 96%